2003
DOI: 10.1063/1.1597956
|View full text |Cite
|
Sign up to set email alerts
|

Infrared emission from zinc sulfide: Rare-earth doped thin films

Abstract: Infrared (IR) electroluminescent (EL) thin film phosphors were radio frequency magnetron sputter deposited by cosputtering of an undoped ZnS target together with ZnS: 1.5 mole % ErF3 or ZnS: 1.5 mole % NdF3 targets. The ZnS:ErF3 and ZnS:NdF3 thin film phosphors were annealed in a N2 ambient at temperatures ranging from 350 to 475 °C for 1 h to increase radiance. The maximum EL radiance observed was 28 μW/cm2 at 1550 nm for ZnS:ErF3, and 26 μW/cm2 at 910 nm and 15 μW/cm2 at 1060 nm for ZnS:NdF3 (at 40 V above t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Annealing phosphor films at 425°C for 1 h resulted in a 60% increase in the mean brightness, consistent with the effects of postdeposition annealing reported by Kale et al 20 Hsu et al 21 reported that annealing at temperatures 300°C increased the EL brightness and reduced the concentration of F in ZnS : TbF 3 ACTFELDs. They attributed the increased brightness to a reduction in F and improved film crystallinity.…”
Section: Discussionsupporting
confidence: 86%
“…Annealing phosphor films at 425°C for 1 h resulted in a 60% increase in the mean brightness, consistent with the effects of postdeposition annealing reported by Kale et al 20 Hsu et al 21 reported that annealing at temperatures 300°C increased the EL brightness and reduced the concentration of F in ZnS : TbF 3 ACTFELDs. They attributed the increased brightness to a reduction in F and improved film crystallinity.…”
Section: Discussionsupporting
confidence: 86%
“…After the phosphor was deposited, dopant activation was performed by annealing the multilayer stack at 425 o C in UHP N 2 for 1 hour. This annealing temperature was found to be optimal, and to significantly increase the infrared output of RF magnetron sputtered ZnS:ErF 3 phosphor films [4,5]. The order of annealing and deposition of the top insulator and could be reversed without noticeable detriment to device performance.…”
Section: Phosphor Deposition and Annealingmentioning
confidence: 99%
“…[2][3][4] Applications of near-infrared emitters include telecommunications, phototherapy, chemical detection, friend-foe identification, and other night-vision technologies. ACTFEL displays exhibit high contrast, wide viewing angle, fast response time, low power, long operating life, crisp images, and the capability for very high resolution, which have all led to commercially available visible light emitting ACTFEL displays 1 while prototype devices emitting in the near infrared have been reported.…”
Section: Introductionmentioning
confidence: 99%